Induced mutagenesis in janeiro grass by ethyl-meta-sulfonate and its effect on spittlebug control - Gómez Villalva, Juan; Cobos Mora, Fernando; Hasang Moran, Edwin; Eguiluz de la Barra, Ana; Cortez Herrera, Israel (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
In this research, the median lethal dose (LD50) and resistance to spittlebug (Mahanarva andigena) were determined, using a mutagenizing agent ethyl meta-sulfonate (EMS) in Janeiro grass (Eriochloa polystachya Kunth) as a means to generate mutations. The study was carried out at the laboratory and greenhouse level, using a Complete Random Design (DCA) with ten treatments and three repetitions, which consisted of 5 doses of EMS (0.00%, 0.25%, 0.50%, 0.75% and 1.00%). for 2 impregnation times (24 and 48 hours). According to the results, the doses of ethyl meta-sulfonate (EMS) influenced the setting of the stolons of the janeiro grass, presenting a high rate of deflation in doses higher than 0.50%. Treatments with doses of 0.25% EMS at 48 hours achieved the best agronomic performance up to 95 days, where plant height had its best development with use close to that determined as DL50 (0.32%). The janeiro grass impregnated with EMS presented slight damage caused by the spittle.